SMARTPHONES AND THE EFFECT OF ITS USE IN EARLY CHILDREN ON STUDENTS' LEARNING INTEREST - Rita Hartati; Muthoifin Muthoifin; Mutohharun Jinan (Profetika: Jurnal Studi Islam, 2023)
This study aims to determine the effect of smartphone use in early childhood on interest in learning in the pandemic era. The subject of this research is at Permata Hati Kids Kindergarten, Delanggu Klaten School. This study used a qualitative approach, the data were collected using the methods of observation, interviews, documentation and google forms. While the data analysis techniques used to describe the results of the research in a structured manner are data collection, data reduction, data presentation and conclusion drawing. Based on the results of the research above, it shows that children are happy playing smartphones and are lazy when invited to study, children prefer to watch YouTube rather than do assignments. Besides that, children are addicted to playing smartphones for a long time, making them lazy to study and do activities. Children also tend to be lazy, to think, because by looking at their smartphones, they find it easy to get what they want. The role played by parents to restore enthusiasm in increasing children's learning interest is that parents must act as role models, children's mirrors and facilitators.